Analisis SWOT Dan Strategi Pemasaran Usaha Waralaba : Studi Kasus Pada Cokelat Klasik Palangka Raya - Sundari, Sundari; Riadi, Eko; Alexandro, Rinto; H, Fendy Hariatama; Merisa Oktaria (FKIP, Universitas Palangka Raya, 2022)
Basically, SWOT analysis is a method used by companies to formulate business strategies to outperform competitors in business competition. By knowing the internal strengths and weaknesses of the company and the strengths and weaknesses of competitors, so that the company can win its competition. This research has the aim of analyzing its SWOT and the marketing strategy applied by Cokelat Klasik. The research method used is qualitative with a case study approach. Data collection techniques through observation, interviews, documentation, and literature study. The data analysis technique used is descriptive. The results showed that Cokelat Klasik business partners have used SWOT analysis, can use the following alternative strategies: SO: continue to innovate and emphasize the concept of modern youth, maintain the quality of drinks, and provide good and maximum service to consumers. ST: Maintaining quality and customer satisfaction, delivery services, buying a generator. WO strategy: competitors as motivation, giving consumers the option to choose products, using promotional media, adding toppings to each drink, reporting consumer complaints about products to the franchisor. WT strategy: Setting competitive prices but not harming partners, always making innovations to differentiate themselves from their competitors. Meanwhile, Cokelat Klasik has applied SWOT analysis into a business strategy in developing its business and gaining an advantage in its business competition